Strategy Marketing Bureau Service Advertisingin Build Trust Customer (Studies Case Pt. Moncoleco (Kuncoro) - Devi, Nurwulan Kusuma; Wibowo, Hadi Mulyo; Hidayat, Rahmat; Naser, Haspul (International Journal of Economics Studies, 2024)
The research aiming to find out how companies run their business, identify strengths, weaknesses, opportunities and threats, and offered solutions. The importance of SWOT analysis, in an effort to overcome the problem of customer trust US a whole to identify the strengths, weaknesses, opportunities and threats faced by PT. Mondoleko Kuncoro. This research is qualitative with a case study approach with a descriptive design. Primary data in the form of interviews, observations, and documentation. The analysis technique uses source triangulation and SWOT analysis. The results showed that PT. Mondoleko Kuncoro runs a business that includes understanding customer needs, building service excellence, relationship marketing, personal selling and direct marketing, and pricing services. The IFAS score was 5.1, while the EFAS was 5.95. The mapping position is in a stable state, meaning that there is no change in its activity, while the SWOT quadrant places it in positions I and III. This shows PT. Mondoleko Kuncoro is still on the verge of weaknesses, but has the strength to take advantage of opportunities.